GAMBARAN TINGKAT STRES AKADEMIK MAHASISWA KEPERAWTAN DALAM MENYUSUN SKRIPSI - Hesti Helpiyani; Jumaini Jumaini; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Academic stress is a feeling of discomfort experienced by students due to the demands of the campus which triggers physical, psychological, and behavioral changes. One of the demands faced by final level students is the process of preparing a thesis. This results in students experiencing academic stress while preparing a thesis. This study aims to determine the description of the academic stress level of nursing students in preparing a thesis. The design of this study used descriptive cross sectional approach. Samples were taken with a total sampling technique of 75 respondents. The measuring instrument uses a Likert scale. The results of this study found that the academic stress levels of students in compiling the thesis were 38 people (50.7%) had severe academic stress levels, namely phased revision of the thesis 55 people (73.3%) and the proposal stage 4 people (5.3%). While the academic stress level is as many as 37 people (49.3%), namely staged data collection 7 people (9.3%) and data processing stages 9 people (12.0%). Stress on physical condition 45 people (60.0%), stress on emotional conditions 59 people (78.7%) and stress on cognitive conditions 46 people (51.3%) were at moderate academic stress levels and stressed on behavioral conditions as much as 30 people (40.0%) were at the level of severe academic stress. It is expected that students who are preparing a thesis must prepare themselves physically and psychologically in preparing a thesis so that they can prevent stress due to thesis.Keyword : educational stress, study of nursing, thesis